1987
DOI: 10.1002/qj.49711347712
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Diurnal Variation of Stratocumulus Using A Multiple Mixed Layer Model

Abstract: A multiple mixed layer model of the cloud-topped boundary layer is developed to investigate the diurnal variation of stratocumulus. A simple representation of the microphysical properties of the cloud layer is included which enables high resolution, interactive radiation calculations to be made. A constraint on the buoyancy flux profile is introduced which permits the previously well-mixed layer to separate into two independently driven layers, thereby avoiding many of the unrealistic aspects of single-layer m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(55 citation statements)
references
References 45 publications
6
49
0
Order By: Relevance
“…In the nocturnal cases, the z is larger (indicating stronger decoupling) in the POC than the surrounding OVC region. In the one daytime flight (RF13), the OVC is more decoupled, consistent with observational and LES studies that find that solar insolation strongly decouples the daytime overcast boundary layer (Turton and Nicholls, 1987;Bretherton et al, 2004;Caldwell and Bretherton, 2009). Although Wood et al (2011a) POC was well mixed ( z = 86 m), we find that this feature is not shared across the other POC cases.…”
Section: Decouplingsupporting
confidence: 82%
“…In the nocturnal cases, the z is larger (indicating stronger decoupling) in the POC than the surrounding OVC region. In the one daytime flight (RF13), the OVC is more decoupled, consistent with observational and LES studies that find that solar insolation strongly decouples the daytime overcast boundary layer (Turton and Nicholls, 1987;Bretherton et al, 2004;Caldwell and Bretherton, 2009). Although Wood et al (2011a) POC was well mixed ( z = 86 m), we find that this feature is not shared across the other POC cases.…”
Section: Decouplingsupporting
confidence: 82%
“…3. 10a, 12a) and in agreement with a typical marine boundary layer (Turton and Nicholls 1987). A closer look at the 24-h harmonic amplitude reveals the details of the model overestimation (Figs.…”
Section: B Diurnal Cyclesupporting
confidence: 78%
“…Each LES still has a suite of microphysical, subgrid turbulence, surface flux and radiation parameterizations and schemes for advecting scalars and velocity that can have significant discretization errors in regions with sharp property gradients such as the capping inversion atop a typical marine stratocumulus cloud layer. Past GASS LES intercomparisons have shown that for stratocumulus under a strong inversion, the cloud thickness is sensitive to grid resolution, advection, and subgrid turbulence schemes [e.g., Bretherton et al, 1999;Stevens et al, 1995;Cheng et al, 2010], and for all precipitating boundary-layer cloud types, the cloud properties are sensitive to microphysical parameterizations [e.g., Ackerman et al, 2009;vanZanten et al, 2011]. Thus another important goal within CGILS is to assess whether the clouds simulated by different LESs all respond in a similar way to a given climate perturbation, and if so, what this might reveal about key mechanisms of subtropical low cloud feedback on climate change.…”
Section: Cgils and Its Les Componentmentioning
confidence: 99%